Development of Attitude Scale Towards the Use of Technology in Primary School Science Course - Ferhat Karakuş (Ömer Gökhan Ulum, 2023)
The aim of this research is to determine the attitudes of 3rd and 4th grade students towards the use of technology in science lessons during the 3rd and 4th centuries. The study utilised a quantitative research method employing a survey design. An attitude scale comprising 30 items was developed using a 3-point Likert scale, including options such as "yes," "no," and "sometimes," suitable for primary school students. After the preliminary application and expert opinions, the items of the scale were revised, resulting in a reduced scale consisting of 23 items. The 23-item scale was administered to a sample of 269 students randomly selected from 3rd and 4th grade students attending Konya Central Primary Schools. Following the analysis of the collected data, the scale was further reduced to 10 items. The Kaiser-Meyer-Olkin value, which assesses the applicability of the scale to factor analysis for determining construct validity, was found to be 0.95. The scale items exhibited factor loads ranging from 0.72 to 0.90, indicating a unidimensional structure that accounted for 67% of the total variance. To evaluate the reliability of the scale, the internal consistency coefficient (Cronbach's alpha) was computed and yielded a value of =0.944, indicating high reliability. Consequently, a valid and reliable attitude scale was successfully developed to assess the attitudes of 4th grade students in primary schools towards the use of technology in science lessons, contributing to the existing literature in this field.